Co-occurring substance use and mental disorders among adults with opioid use disorder - Jones, Christopher M.; McCance-Katz, Elinore F. (Drug and alcohol dependence, 2019)
•Co-occurring substance use and mental disorders are common among adults with OUD.•Receipt of both mental health and substance use disorder treatment is suboptimal.•Expansion of comprehensive care models for co-occurring disorders are needed. Co-occurring substance use and mental disorders among people with opioid use disorder (OUD) increase risk for morbidity and mortality. Addressing these co-occurring conditions is critical for improving treatment and health outcomes. There is limited recent research on the prevalence of co-occurring disorders, demographic characteristics associated with co-occurring disorders, and receipt of mental health and substance use treatment services among those with OUD. This limits the development of targeted and resourced policies and clinical interventions. Using 2015–2017 National Survey on Drug Use and Health data, prevalence of co-occurring substance use and mental disorders and receipt of mental health and substance use treatment services was estimated for adults aged 18–64 with OUD. Multivariable logistic regression assessed demographic and substance use characteristics associated with past-year mental illness (AMI) and serious mental illness (SMI) among adults with OUD as well as treatment receipt. Among adults with OUD, prevalence of specific co-occurring substance use disorders ranged from 26.4% (95% CI:23.6%–29.4%) for alcohol to 10.6% (95% CI:8.6%–13.0%) for methamphetamine. Prevalence of AMI was 64.3% (95% CI:60.4%–67.9%) and SMI was 26.9% (95% CI:24.2%–29.8%). Receiving both mental health and substance use treatment services in the past year was reported by 24.5% (95% CI:21.5%–29.9%) of adults with OUD and AMI and 29.6% (95% CI:23.3%–36.7%) of adults with OUD and SMI. Co-occurring substance use and mental disorders are common among adults with OUD. Expanding access to comprehensive service delivery models that address the substance use and mental health co-morbidities of this population is urgently needed.